Minimally Invasive Surgery for Achilles Tendon Disorders in Clinical Practice - Maffuli, Nicola; Easley, Mark.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Minimally Invasive Surgery for Achilles Tendon Disorders in Clinical Practice is a collection of procedures presented by experts and pioneers in foot and ankle surgery who share an interest in developing less invasive methods of treating disorders of the foot and ankle. The rate of complications of traditional surgery is extremely high: in the management of tendinopathy, traditional techniques result in 10% of patients experiencing a complication related to skin healing. It is therefore not surprising that less invasive techniques have been advocated. This book will serve as an excellent pocket reference when repairing disorders of the Achilles and aimed general orthopedic surgeons and specialist who require a useful easy reference for these procedures.
Keywords: Orthopedics; Orthopedics; Surgical Orthopedics